Raman amplifier based long-distance, remote FBG strain sensor with EDF broadband source recycling residual Raman pump - Lee, JH; Han, YG; Chang, YM; Lee, SB (IEE-INST ELEC ENG, 2004)
A novel and simple Raman amplifier based long-distance fibre Bragg grating (FBG) sensing system without any additional broadband light source is demonstrated. With the simplified system configuration recycling residual Raman pump power for generation of amplified spontaneous emission in an erbium-doped fibre (EDF), the high quality of remote strain sensing operation at a location of 50 km is achieved.
Keywords: TEMPERATURE